The diversification benefits from Islamic investment during the financial turmoil: the case for the US-based equity investors - Saiti, Buerhan; Bacha, Obiyathulla Ismath; Masih, Mansur (Elsevier, 2014)
A major issue in both Islamic finance and conventional finance is whether the shocks to the volatilities in the asset returns are substitutes or complements in terms of taking risk. An understanding of how volatilities of and correlations between asset returns change over time including their directions (positive or negative) and size (stronger or weaker) is of crucial importance for both the domestic and international investors with a view to diversifying their portfolios for hedging against unforeseen risks.